Penerapan Model Team Assisted Individualization (TAI) Berbasis Media Digital dalam Meningkatkan Kompetensi Pembelajaran Naḥwu - Ch, Hendrawanto; Masyitoh, Siti; Haniefa, Rifda (Al-Ma‘rifah, 2025)
This study aims to examine the effectiveness of implementing the Team Assisted Individualization (TAI) model integrated with digital media in improving naḥwu (Arabic grammar) learning competence at the Arabic Language Education Program, Universitas Negeri Jakarta. The TAI model combines individual learning with structured group collaboration and, in this study, is integrated with three main digital platforms: Educaplay, Aljazeera Learning, and Learning Management System (LMS). A quantitative approach was employed using a pre-experimental one-group pretest-posttest design. The sample consisted of 25 second-semester students selected through purposive sampling. Statistical analysis showed a significant increase in the average scores from pretest (71.30) to posttest (89.40), with a paired sample t-test result of 0.000 (p < 0.05). The implementation of digital-based TAI positively impacted students’ understanding of syntactic structures, fostered active engagement, and strengthened both collaborative and independent learning. The integration of digital media enriched the learning process through visualization, interactivity, and authentic Arabic language resources. The findings suggest that the digital TAI model is a viable and innovative instructional strategy for naḥwu learning in higher education, aligning with the characteristics of 21st-century learners.